1957
DOI: 10.3181/00379727-95-23148
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Foot-and-Mouth Disease Virus by pH and Temperature Changes and by Formaldehyde

Abstract: 147 ganisms and without cross-resistance to the majority of other clinically useful an ti biotics. Oleandomycin is an agent which, with the exception of cross-resistance to members of the erythromycin group, displays these properties.Summary (1) In vitro under the specific conditions of the gradient plate technic, combinations of sulfisoxazole and oleandomycin in specific ratios show an activity superior to that observed with the single constituents.( 2 ) Supplemental activity was also observed in vivo in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0

Year Published

1958
1958
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(56 citation statements)
references
References 0 publications
4
52
0
Order By: Relevance
“…Lauffer & Wheatly (1951) re-investigated the problem of the alleged 3/2 order reaction with influenza haemagglutinin and concluded that the behaviour of their virus was conditioned by the presence, in even the most highly purified preparations, of a mixture of rapidly and slowly reacting haemagglutinin particles. Bachrach, Breese, Callis, Hess & Patty (1957) showed that foot-and-mouth disease virus has a heat inactivation pattern very similar to that found by us for vaccinia, Our results suggest that vaccinia virus preparations also contain particles C . Kaplan with two or three sensitivities to heat, It is more likely, however, that a given vaccinia virus population contains a great preponderance of particles which are rapidly inactivated and a smaller proportion of varying susceptibility to heat.…”
Section: Discussionsupporting
confidence: 69%
“…Lauffer & Wheatly (1951) re-investigated the problem of the alleged 3/2 order reaction with influenza haemagglutinin and concluded that the behaviour of their virus was conditioned by the presence, in even the most highly purified preparations, of a mixture of rapidly and slowly reacting haemagglutinin particles. Bachrach, Breese, Callis, Hess & Patty (1957) showed that foot-and-mouth disease virus has a heat inactivation pattern very similar to that found by us for vaccinia, Our results suggest that vaccinia virus preparations also contain particles C . Kaplan with two or three sensitivities to heat, It is more likely, however, that a given vaccinia virus population contains a great preponderance of particles which are rapidly inactivated and a smaller proportion of varying susceptibility to heat.…”
Section: Discussionsupporting
confidence: 69%
“…The utility of the half-life period will be limited, of course, if a virus population is heterogeneous with respect to its pH stability, as shown for example by Bachrach et al (1957) for foot-and-mouth disease virus at pH 5 and 6. We did not obtain any evidence that rinderpest virus exhibits any such heterogeneity.…”
Section: Resultsmentioning
confidence: 99%
“…This, for example, may be compared with the different stabilities of small RNA viruses-high in the case of polioviruses (Bachrach & Schwerdt, 1952) and low in the case of foot-andmouth disease (Bachrach et at. 1957).…”
Section: Resultsmentioning
confidence: 99%
“…Heat inactivation of viruses represents an important approach for mitigating the risk of viral contamination for food and drinking water protection [1][2][3][4][5][6][7][8][9][10], inactivation of vaccine viruses [11][12][13][14][15], inactivation of viruses of importance to agriculture and animal husbandry [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30], and inactivation of viruses in blood products [31][32][33]. More recently, heat inactivation and more particularly high-temperature short-time (HTST) treatment have been evaluated as a barrier technology for mitigating the risk of introducing adventitious viral contaminants into biologics manufacturing processes through contaminated cell culture reagents [34][35][36].…”
Section: Introductionmentioning
confidence: 99%